Enhanced Onos Sdn Controllers Deployment For Federated Multi-Domain Sdn-Cloud With Sd-Routing-Exchange - Risdianto, Aris Cahyadi; Tsai, Pang-Wei; Ling, Teck Chaw; Yang, Chu-Sing; Kim, JongWon (Malaysian Journal of Computer Science, 2017)
The requirement of auto provisioning, administration, management and governing of networking resources in distributed environment, which spreads over multiple administrative domains (i.e., multi-domain) is a challenging task. This paper demonstrates an effort to inter-connect distributed SDN-Cloud resources which spread over three administrative domains in three different countries on OF@TEIN Playground. The proposed SD-Routing-Exchange utilizes BGP routing protocol as control-plane for federated multi-domain SDN-Cloud data-plane. This method has improved the flexibility of networking control, and provides reasonable interconnections redundancy and performance enhancement.